When work doesn't work anymore : women, work and identity - McKenna, Elizabeth Perle (New York : Delacorte Press, 1997)
In this groundbreaking book, the author challenges the outdated system of work for professional women, and encourages readers to re-examine work as their sole identities, and, if they are unhappy, to allow room for their lives. Elizabeth Perle McKenna, a former publishing executive, explores women's relationship with work. For decades, women have succeeded at traditional male jobs, but now, deep in the second stage of the feminist movement, they want lives that are integrated and whole. Based on original research and containing hundreds of interviews with prominent working women, this book exposes the inherent conflict between the way work traditionally is structured and rewarded, and what women desire and value in their lives. It suggests new ways for women to identify their values, reclaim their identities, and define success on their own terms. The author also deconstructs the myth that women can have it all, and shows that they risk true happiness until they give up that impossible ideal. Her focus extends to every working woman who will most likely face a life-altering situation at some point in her career and will need to redefine what success means to her.
1. Great expectations -- 2. When work becomes identity -- 3. The price of success -- 4. When work stops working -- 5. Resistance at the turning point -- 6. The importance of money -- 7. Changing -- 8. Work that works -- 9. Men, work, and identity -- 10. Balance and meaning .
Includes index.
Keywords: WOMEN -- UNITED STATES -- PSYCHOLOGY